Structural Equation Modeling: The Influence of School Environment on Students' Interest in Selecting State University - Simarmata, Justin Eduardo; Mone, Ferdinandus; Chrisinta, Debora (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
Despite prior research on student interest in colleges, this study focuses specifically on how the school environment, including individual factors, friends, and teachers, influences students' interest in attending a state university. Understanding these influences can help improve educational systems to better guide students towards higher education. This study aims to determine the influence of the school environment on students' interest in selecting a state university. This research employs a quantitative approach, utilizing structural equation modeling to analyze the relationships between variables. This study examines how a school environment, captured by twelve indicators across individual, friend, and teacher influences, impacts students' interest in state universities. Therefore, data retrieval based on questionnaires is designed accordingly based on latent variables. The sample in this study were 474 high school and vocational school students on the Indonesia-Timor Leste border, which is precisely located in Timor Tengah Utara Regency. The results showed that the school environment that came from individuals, partners, and teachers had a major influence on students' interest in choosing State University. Based on the analysis of structural equations, it was found that individual environments had a direct influence of 98%, partner environments had an indirect influence of 90%, and teachers also indirectly affected 71%. This study contributes to the field by quantifying the distinct influences of individual, peer, and teacher aspects of the school environment on students' interest in attending state universities. This knowledge can inform the development of targeted interventions to improve educational guidance and support student decision-making.